Distinct VIP and PACAP Functions in the Distal Nerve Stump During Peripheral Nerve Regeneration - Woodley, Patricia K.; Min, Qing; Li, Yankun; Mulvey, Nina F.; Parkinson, David B.; Dun, Xin-peng (Frontiers in Neuroscience, 2019)
Vasoactive Intestinal Peptide (VIP) and Pituitary Adenylyl Cyclase Activating Peptide (PACAP) are regeneration-associated neuropeptides, which are up-regulated by neurons following peripheral nerve injury. So far, they have only been studied for their roles as autocrine signals for both neuronal survival and axon outgrowth during peripheral nerve regeneration. In this report, we examined VIP and PACAP’s paracrine effects on Schwann cells and macrophages in the distal nerve stump during peripheral nerve regeneration. We show that VPAC1, VPAC2 and PAC1 are all up-regulated in the mouse distal nerve following peripheral nerve injury and are highly expressed in Schwann cells and macrophages within the distal sciatic nerve. We further investigated the effect of VIP and PACAP on cultured rat Schwann cells, and found that VIP and PACAP can not only promote myelin gene expression in Schwann cells but also can inhibit the release of pro-inflammatory cytokines by Schwann cells. Furthermore, we show that VIP and PACAP inhibit the release of pro-inflammatory cytokines and enhance anti-inflammatory cytokine expression in sciatic nerve explants. Our results provide evidence that VIP and PACAP could have important functions in the distal nerve stump following injury to promote remyelination and regulate the inflammatory response. Thus, VIP and PACAP receptors appear as important targets to promote peripheral nerve repair following injury.